Homilies on Jeremiah : Homily on 1 Kings 28 - Origen (Fathers of the church ;, 1998)
Presented in this volume are the remains of twenty-two homilies and a collection of fragments delivered by Origen around A.D. 240. The original texts of the homilies on Jeremiah have not come down to us completely; two of the homilies survive only in a Latin translation of St. Jerome. The homily on 1 Kings 28, while not a part of the homilies on Jeremiah, deals with the Witch of Endor and has been added to this volume in virtue of its own inherent interest.